Bioactive Characteristics of Wild Berberis vulgaris and Berberis crataegina Fruits - Eroglu, Arzu Yasar; Cakir, Ozlem; Sagdic, Mustafa; Dertli, Enes (HINDAWI LTD, 2020)
There is an increasing trend to find novel sources of products with high antioxidant capacity and wild fruits are very good examples for these sources. In this study, fruits ofBerberis vulgarisandBerberis crataegina, naturally grown in Bayburt province of Turkey, were tested for their physicochemical features, antioxidant capacities, phenolic compound profiles, and antimicrobial activities. The physicochemical analysis of the fruits revealed that the dry matter content, ash content, pH, anda(w)values were between 28.47% and 41.61%, 0.65% and 2.13%, 2.44 and 3.25, and 0.996 and 0.97, respectively. The total phenolic content of the fruits was determined by the Folin-Ciocalteu methodology, and for the determination of the antioxidant capacity of the fruits, DPPH, ABTS, and beta-carotene bleaching methods were performed and a high level of antioxidant activity was observed. HPLC analysis was applied to identify the phenolic content of the fruits, and gallic acid and chlorogenic acid were found to be the dominant phenolic compounds inBerberisfruits. The water extracts of theBerberisfruits were tested against important foodborne pathogenic bacteria as potential antimicrobials. The extracts inhibited the growth ofBacillus cereus,Salmonella typhimurium,Yersinia enterocolitica, andStaphylococcus aureusat significant rates. This study revealed the potential antioxidant and antimicrobial characteristics of wild-typeB. vulgarisandB. crataeginathat can be used for different future applications.
Keywords: ANTIOXIDANT CAPACITY; L. FRUITS; Chemistry